Relationship between sleep patterns, bedtime and recurrent aphthous stomatitis (RAS) during the COVID-19 pandemic: analytical observational research - Saputro, Septian Adi; Arifta, Arum Nur; Medawati, Ana; Andriani, Ika; Rahmawati, Atiek Driana; Femilian, Afryla; Perdana, Lutfi Putra (Universitas Padjadjaran, 2024)
Introduction: Recurrent Aphthous Stomatitis (RAS) is an inflammation on the oral mucosa, presenting as recurrent, round, single, or multiple ulcers with well-defined boundaries. Although the exact etiology of RAS remains unknown, several factors are known to contribute to its development. During the COVID-19 pandemic, various problems have arisen, especially among adolescents, including senior high school students, whose sleep patterns-specifically their sleep time, duration, and quality-have been disrupted. These disruptions may weaken their immune system, making them more susceptible to RAS disease. The objective of this study is to analyze the relationship between sleep patterns, bedtime, and the occurrence of RAS during the COVID-19 pandemic. Method: The research design employed was an analytical observational study, with a cross-sectional approach. Purposive sampling was used to select all class XI students of SMA 6 Yogyakarta, based on inclusion and exclusion criteria. The research instruments included the PSQI questionnaire (used to measure sleep patterns, sleep time, sleep duration, and sleep quality) and the RASDX questionnaire (a diagnostic tool for measuring the prevalence of RAS lesions) both administered via Google Forms. Statistical analysis was conducted using the Chi-square test. Results: A total of 58 students (55.8%) experienced RAS, with a higher prevalence among female students. Regarding age, 16-year-old students had the highest incidence of RAS, with 79 students (64.4%) affected. Most respondents, 79 respondents (76%), were reported to have good sleep patterns. The results of the bivariate analysis also revealed a significant relationship between sleep patterns, bedtime, and the occurrence of RAS (p=0.043<0.05). Conclusion: Sleep patterns, bedtime, and the occurrence of RAS were found to be interrelated during the COVID-19 pandemic.